Learning Mathematics with Creative Drama - Baki Şahin (Araştırma Temelli Etkinlik Dergisi, 2018)
In this study, a mathematics activity that used creative drama method to teach the fifth grade standard “Expresses a position with respect to another point using direction and unit” under geometry and measurement was implemented. Twenty students attending the fifth grade of a public school participated in the study. The lesson plan involved four activities in warm-up, role-play, and evaluation stages. Activities include processes that will ensure active participation of students. The activity lasted two lesson hours. Two prospective mathematics teachers and a mathematics teacher were available in the class during the activity to observe student participation and reactions. Additionally, 10 students were interviewed to learn their views about the lesson. Comments of the observers and the responses of the students to the interview questions indicate that the lesson was successful.